Vibronic Spectra of π-Conjugated Systems with a Multitude of Coupled States: A Protocol Based on Linear Vibronic Coupling Models and Quantum Dynamics Tested on Hexahelicene - Aranda, Daniel; Santoro, Fabrizio (ACS Publications, 2021)
Hexahelicene is a prototype of an extended π-conjugated system with axial chirality. Its absorption (ABS) and electronic circular dichroism (ECD) spectra show vibronic features and strong nonadiabatic effects, challenging currently available computational methods. Here, we compute the nonadiabatic ABS and ECD vibronic spectra of hexahelicene in the full energy range, covering ∼2 eV and 14–18 coupled electronic states, including all of the relevant nuclear coordinates. To this end, we exploit a recently proposed protocol that uses time-dependent density functional theory to parameterize linear vibronic coupling models comprising several electronic states. Spectra are computed through quantum dynamical propagations with multiconfigurational time-dependent Hartree methods. Our results nicely reproduce the experimental spectra providing an assignment of the main observed bands. On the contrary, we document that the application of the Herzberg–Teller intensity-borrowing theory leads to large artifacts. The proposed approach is of general applicability for rigid systems and represents a viable tool for studying the photophysical properties of π-conjugated systems characterized by a dense manifold of interacting electronic states.
Keywords: Electrónica - Espectros; absorption; electronic circular dichroism; nonadibatic effects; quantum dynamics; helicenes